2007
DOI: 10.1111/j.1365-2664.2007.01320.x
|View full text |Cite
|
Sign up to set email alerts
|

Using adaptive management to determine requirements of re‐introduced populations: the case of the New Zealand hihi

Abstract: Summary 1.Adaptive management involves the development of predictive models, strategic manipulation of management actions to gain information, and subsequent updating of the models and management. The paradigm has several characteristics that make it an effective approach for determining requirements of re-introduced populations. 2. Adaptive management was applied to the re-introduction of hihi Notiomystis cincta , a New Zealand forest bird that had been reduced to a single island population. Following three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
125
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 32 publications
3
125
0
1
Order By: Relevance
“…Most management programs do not explicitly record and incorporate failures or observations that disagree with a preconceived notion of system function (see Armstrong et al 2007). In the framework we provide, our certainty in each model of system function is explicitly incorporated, such that all potential models of system function are evaluated in deciding how best to manage.…”
Section: Discussionmentioning
confidence: 99%
“…Most management programs do not explicitly record and incorporate failures or observations that disagree with a preconceived notion of system function (see Armstrong et al 2007). In the framework we provide, our certainty in each model of system function is explicitly incorporated, such that all potential models of system function are evaluated in deciding how best to manage.…”
Section: Discussionmentioning
confidence: 99%
“…The interacting ecologic factors that limit the long-term survival of the populations may vary (Armstrong et al, 2002). To compensate for the lack of natural cavities in restored forest habitat, nest boxes have been provided at translocation sites (Armstrong et al, 2007) and it has been necessary to control nest mites (Ornithonyssus spp. ), which can cause nestling deaths (Armstrong et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, food availability is the only factor that has been found experimentally to affect population growth (Castro et al, 2003;Armstrong et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Parasites are frequently observed in nestling birds and can have a severe impact on their health, condition, and immediate survival (1), potentially even causing populations to decline (2,3). It is not surprising therefore, that parasite-induced mortality is a major selection pressure on nestling growth and development time (4).…”
mentioning
confidence: 99%
“…We have previously shown that enhanced carotenoids have little effect on hatchability of eggs, nestling survival, or nestling immunity in parasite controlled environments (21). To introduce a natural stressor to the nest environment we manipulated exposure of nestlings to the bloodsucking mite (Ornithonyssus bursa), a common parasite of hihi (2). O. bursa are known to alter host behavior and detrimentally effect host fitness in some species (22,23).…”
mentioning
confidence: 99%